Single Centre Prospective Study of Systematic Pain Evaluation in Portuguese Patients with Metastatic Prostate Cancer - Sequeira, Maria Inês (2017)
Introduction: Pain is one of the most common symptoms reported by cancer patients and is associated with decreased quality of life. Assessment of pain with standardized questionnaires reduces variability in its interpretation and may increase effectiveness of medical interventions. Prostate cancer is the most frequent male neoplasm in Portugal. We designed this study to evaluate the impact of a standardized pain questionnaire on pain management in patients with metastatic prostate cancer.Material and Methods: Single centre prospective observational study of patients with metastatic prostate cancer. The study was designed to evaluate the benefit of systematically evaluating pain with Brief Pain Inventory-Short Form prior to a scheduled medical oncology consult. Patients reporting pain were reassessed one week later by telephone. To assess the benefit two consecutive cohorts were established based on communication of questionnaire results to the treating physician.Results: We recruited 207 patients of which 60% reported pain. Statistically significant decrease in mean pain intensity one week after the scheduled appointment was noted (3.95 vs 3.01; p < 0.001). Patients whose Brief Pain Inventory-Short Form was provided to their oncologist experienced greater reduction in pain, which was non-significant (p = 0.227). Using Brief Pain Inventory-Short Form assessment resulted in a higher probability of pain control (43.5% vs 30.9%; p = 0.193).Discussion: The prevalence of pain founded was higher than described in the literature, probably because our sample was less selected than the published in clinical trials. After the scheduled appointment, there was a statistically significant reduction in mean pain intensity, but the explicit use of this questionnaire was not associated with a statistically significant reduction of pain.Conclusion: Patients with metastatic prostate cancer have a high prevalence of pain. Evaluation and treatment by medical oncologists is associated with a reduction of mean pain intensity. The use of Brief Pain Inventory-Short Form was associated with a non-significant increased reduction of pain.